L’identité professionnelle et la professionnalisation des IEN en France : entre normes prescrites et appropriation - Lydia Bouhila; Jean-François Marcel (Questions Vives)
This article targets the French National Education Inspectors (IEN), who are senior officials in the primary education system with authority over schoolteachers. They are responsible for implementing national and academic policies and have administrative and pedagogical oversight of a district. Our research examines their professionalization through the appropriation of professional norms. It involves analyzing, on one hand, the characteristics of the IEN as expected by the institution, and on the other hand, the professional identity of the IEN in the field. The narratives of the IEN highlight the factors of professionalization. Our conclusions reveal conservative values of the prescribed identity. The IEN must maintain a certain appearance, demonstrate strategic reasoning, and adopt a managerial position representing the institution. The IEN manages to appropriate these norms by showing “openness to change” and “self-transcendence” (Schwartz, 2006) in the service of others. Hierarchical recognition also acts by conferring a sense of legitimacy. When put to work, the unique aspects of personal identity generate professionalization.